Determining the Suitability of Various Surface Treatment Methods with the Control of Blasting Time with Respect to the Quality of Powder Coating - Neškudla Michal; Jeníček Lukáš; Malaťák Jan (Acta Technologica Agriculturae, 2023)
The paper is focused on steel surface processing to ensure an improved adhesion of applied powder layer. Mechanical pre-treatment, chemical pre-treatment and their combination were used to compare their results with each other and to find out the pre-treatment that affected the final outcome the most. The final score was determined by the grid method. The outcome displayed a huge mutual dependency between the result and a kind of various surface treatments. The method with no pre-treatment was by far the worst, followed by the mechanical pre-treatment only, followed by the chemical pre-treatment only, and finally by their combination. The time of blasting affects the final outcome. Through the grid method, coating thickness, and aesthetic test it was confirmed that an optimal blasting time of 5 min provides the best outcome.